Mixed germ cell tumour of the testicle: a case report of a patient presenting with acute abdomen - Shaik, Abdul Bari; Shaik, Noor Fathima (International Journal of Research in Medical Sciences, 2020)
Testicular tumours are a group of heterogenous neoplasms seen commonly in men between the ages of 15 and 35 years. The two main types are seminoma and non-seminomatous germ cell tumour (NSGCT). Testicular cancers are highly treatable and usually curable, even if they present at an advanced stage of the disease with a five-year survival rate of over 95 percent. The symptoms at initial presentation can vary depending on the metastasis, but a nodule or painless swelling of testicle is usually noted. In this case report we will study how a patient with metastatic testicular tumour presents with symptoms indicative of gastrointestinal infection of acute nature with no associated features. We will review current literature on testicular cancers, reasons for delay in treatment and its impact on patient care.